Center practice drives variation in choice of US kidney transplant induction therapy: a retrospective analysis of contemporary practice. (2nd November 2017) - Dharnidharka, Vikas R.; Naik, Abhijit S.; Axelrod, David A.; Schnitzler, Mark A.; Zhang, Zidong; Bae, Sunjae; Segev, Dorry L.; Brennan, Daniel C.; Alhamad, Tarek; Ouseph, Rosemary; Lam, Ngan N.; Nazzal, Mustafa; et al.
Summary: To assess factors that influence the choice of induction regimen in contemporary kidney transplantation, we examined center‐identified, national transplant registry data for 166 776 US recipients (2005–2014). Bilevel hierarchical models were constructed, wherein use of each regimen was compared pairwise with use of interleukin‐2 receptor blocking antibodies (IL2rAb). Overall, 82% of patients received induction, including thymoglobulin (TMG, 46%), IL2rAb (22%), alemtuzumab (ALEM, 13%), and other agents (1%). However, proportions of patients receiving induction varied widely across centers (0–100%). Recipients of living donor transplants and self‐pay patients were less likely to receive induction treatment. Clinical factors associated with use of TMG or ALEM (vs. IL2rAb) included age, black race, sensitization, retransplant status, nonstandard deceased donor, and delayed graft function. However, these characteristics explained only 10–33% of observed variation. Based on intraclass correlation analysis, "center effect" explained most of the variation in TMG (58%), ALEM (66%), other (51%), and no induction (58%) use. Median odds ratios generated from case‐factor adjusted models (7.66–11.19) also supported large differences in the likelihood of induction choices between centers. The wide variation in induction therapy choice across US transplant centers is not dominantly explained by differences in patient or donor characteristics; rather, it reflects center choice and practice.